2022
DOI: 10.1002/slct.202102694
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Heavy‐Oil Viscosity Reducer Containing a Benzene Ring and Its Viscosity Reduction Mechanism

Abstract: In this study, a small molecular viscosity reducer containing benzene ring was synthesized and evaluated its ability of dispersing asphaltenes and resins. It is helpful for introduction of polar groups to dispersing asphaltene. Benzene ring structure can make viscosity reducer molecules penetrate into the stacking structure of asphaltene and resin better. The long carbon chain in the molecule can interact with paraffin to change the crystalline state of paraffin and reduce the viscosity of heavy oil. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…HA comprises carboxylate groups, which give it a negative charge [ 11 ] and allows it to bind to a large amount of water creating an extremely viscous gel. In ISPR configuration, the mass of adsorbent added to the STR must be sufficient so that the product produced (i.e., HA) can be fully recovered and the broth viscosity can be maintained below the threshold throughout the fermentation process [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HA comprises carboxylate groups, which give it a negative charge [ 11 ] and allows it to bind to a large amount of water creating an extremely viscous gel. In ISPR configuration, the mass of adsorbent added to the STR must be sufficient so that the product produced (i.e., HA) can be fully recovered and the broth viscosity can be maintained below the threshold throughout the fermentation process [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the application of granule-activated carbon and increasing the temperature to an anaerobic digestion system has been shown to reduce the viscosity and, simultaneously, improve the material and energy transfer [ 65 ]. Another study by Yu et al (2022), showed that the VR-1 resin has good viscosity reduction ability for heavy oil [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al synthesized a small molecular viscosity reducer containing benzene rings for heavy crude oil. 12 The study revealed that the benzene ring structure enables better dispersion of the reducer molecules into asphaltene and resins deposition structures. The long carbon chains within the molecules interact with paraffin, altering its crystalline state and reducing the viscosity of the heavy oil.…”
Section: Introductionmentioning
confidence: 97%
“…Oil‐soluble polymer demulsifiers are the most commonly employed agents for improving crude oil flowability, although their high cost remains a focal point of research. Yu et al synthesized a small molecular viscosity reducer containing benzene rings for heavy crude oil 12 . The study revealed that the benzene ring structure enables better dispersion of the reducer molecules into asphaltene and resins deposition structures.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the effects of different metal or metal oxide nanoparticles, including iron, nickel, copper, magnetite, alumina, and titanium dioxide, on the viscosity of heavy oil have been investigated [33][34][35][36]. However, existing nanomaterials are mostly used to catalyze the cleavage of asphaltene structures to achieve viscosity reduction when used in conjunction with viscosity reduction on heavy oil, which needs to be used at high temperatures, and the effect is often not added at low temperatures [37][38][39][40][41][42]. In other studies, silica has been used for viscosity reduction by emulsification, but with some drawbacks.…”
Section: Introductionmentioning
confidence: 99%